ELAVL4, splicing, and glutamatergic dysfunction precede neuron loss in MAPT mutation cerebral organoids - Bowles, Kathryn R.; Silva, M. Catarina; Whitney, Kristen; Bertucci, Taylor; Berlind, Joshua E.; Lai, Jesse D.; Garza, Jacob C.; Boles, Nathan C.; Mahali, Sidhartha; Strang, Kevin H.; Marsh, Jacob A.; Chen, Cynthia; et al. (Cell, 2021)
Frontotemporal dementia (FTD) because of MAPT mutation causes pathological accumulation of tau and glutamatergic cortical neuronal death by unknown mechanisms. We used human induced pluripotent stem cell (iPSC)-derived cerebral organoids expressing tau-V337M and isogenic corrected controls to discover early alterations because of the mutation that precede neurodegeneration. At 2 months, mutant organoids show upregulated expression of MAPT, glutamatergic signaling pathways, and regulators, including the RNA-binding protein ELAVL4, and increased stress granules. Over the following 4 months, mutant organoids accumulate splicing changes, disruption of autophagy function, and build-up of tau and P-tau-S396. By 6 months, tau-V337M organoids show specific loss of glutamatergic neurons as seen in individuals with FTD. Mutant neurons are susceptible to glutamate toxicity, which can be rescued pharmacologically by the PIKFYVE kinase inhibitor apilimod. Our results demonstrate a sequence of events that precede neurodegeneration, revealing molecular pathways associated with glutamate signaling as potential targets for therapeutic intervention in FTD. [Display omitted] •Tau and P-tau accumulation and autophagy disruption in tau-V337M organoids•Accelerated synaptic maturation and loss of glutamatergic cortical-layer neurons•Altered ELAVL4 expression, dysregulated splicing, accelerated synaptic maturation•Rescue of susceptibility to glutamatergic toxicity by PIKFYVE inhibitor apilimod Characterization of iPSC-derived cerebral organoids with the tau-V337M mutation, which causes frontotemporal dementia, reveals changes preceding neuron death as potential targets for therapeutic intervention, as demonstrated by rescue of susceptibility to glutamatergic toxicity by the PIKFYVE inhibitor apilimod.